Strengthening Community Legal Awareness Toward Consumer Protection Laws Through the Utilization of Information Technology - Mahanani, Anajeng Esri Edhi; Aditiawan, Firza Prima; Anggriawan, Teddy Prima (Future Science, 2020)
The development of information technology has had a major impact on the development of the business world. Types of businesses are increasingly diverse, including the types of businesses online. This development is increasing with positive and negative influences in 2020. However, at the beginning of 2020 too, the world economy was shifting due to health issues, namely the covid-19 virus. This health issue has a major influence on the business world online, many cases of business buying and selling of non-National Food and Drug Agency products are even far from the quality they should be. This is only one example of a potential violation of consumer rights. This research aims to disseminate information technology-based media related to the enactment of Law Number 8 of 1999 concerning Consumer Protection. This socialization is packed with technological developments, and a touch of humanism in society and industrial development 5.0, namely through android-based applications. This research is expected to be a form of the contribution of UPN